A sliding-mode variable-structure controller based on exact feedback linearization for automatic navigation system - Xiaoping, Bai; Jingtao, Hu; Tian, Zhang (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: In order to improve the path tracking accuracy and robustness of the agricultural machinery navigation system, a sliding-mode variable-structure controller based on exact feedback linearization was presented. Firstly, based on the differential geometry theory and the affine nonlinear kinematics model, the corresponding nonlinear coordinate change matrix and nonlinear state variable feedback equations were deduced, and an exact feedback linearization model was then established. Secondly, based on the exact feedback linearization model, a sliding-mode variable-structure controller was designed by selecting suitable linear switching function and exponential reaching law. Finally, the comparative experiments were carried out. And the experimental results indicated that the proposed method had a high tracking accuracy and robustness. The maximum lateral error of the straight line tracking was less than 0.06 m, and maximum lateral error of the curve path tracking was less than 0.09 m. Experimental results show that the transplanter based on this automatic navigation system can effectively track the predefined path.Keywords: agricultural machine, affine nonlinear kinematics model, exact feedback linearization, sliding-mode variable-structure controllerDOI: 10.3965/j.ijabe.20160905.1830Citation: Bai X P, Hu J T, Gao L, Zhang T. A sliding-mode variable-structure controller based on exact feedback linearization for automatic navigation system. Int J Agric & Biol Eng, 2016; 9(5): 158－165.